2021
DOI: 10.1016/j.bbrep.2021.101105
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic modifiers of murine hepatic β-glucocerebrosidase activity

Abstract: The acid β-glucocerebrosidase (GCase) enzyme cleaves glucosylceramide into glucose and ceramide. Loss of function variants in the gene encoding for GCase can lead to Gaucher disease and Parkinson's disease. Therapeutic strategies aimed at increasing GCase activity by targeting a modulating factor are attractive and poorly explored. To identify genetic modifiers, we measured hepatic GCase activity in 27 inbred mouse strains. A genome-wide association study (GWAS) using GCase activity as a trait identified sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Gaucher disease (GD) has been an example where it has been continuously analyzed how modifying genes, epigenetics, and other factors can lose the clear limits between simple and complex inheritance [ 73 ]. Durán et al, 2021 found 271 Single Nucleotide Variants (SNVs) within nine genes associated with the hepatic activity of the enzyme β-glucocerebrosidase that causes GD, which could act as modifying the activity of the enzyme [ 74 ]. In Charcot-Marie-tooth disease type 1A (CMT1A), mutations in the LITAF gene can predispose to the appearance of CMT1A for up to 13 years, in contrast with those who do not present the variant [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gaucher disease (GD) has been an example where it has been continuously analyzed how modifying genes, epigenetics, and other factors can lose the clear limits between simple and complex inheritance [ 73 ]. Durán et al, 2021 found 271 Single Nucleotide Variants (SNVs) within nine genes associated with the hepatic activity of the enzyme β-glucocerebrosidase that causes GD, which could act as modifying the activity of the enzyme [ 74 ]. In Charcot-Marie-tooth disease type 1A (CMT1A), mutations in the LITAF gene can predispose to the appearance of CMT1A for up to 13 years, in contrast with those who do not present the variant [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…The advantages of using mouse models in biomedicine have been discussed extensively [ 3 ]. Some benefits are the following: (i) the availability of genetic tools for creating disease models by transgenic, knockout, and knock-in technologies [ 4 , 5 , 6 ] ( (accessed on 22 May 2022)); (ii) inbred mouse strains are nearly isogenic, enabling to study how the same genetic mutation modifies a phenotype of interest in different genetic backgrounds [ 7 , 8 , 9 , 10 , 11 ]; (iii) mouse tissues are available for omics studies which can be challenging to obtain from humans [ 12 ]. Some limitations include different evolutive pressures for mice and humans; therefore, some systems, such as the immune system, do not function similarly in both species [ 13 ].…”
Section: Rodents As Model Organisms In Genetic Research: Advantages A...mentioning
confidence: 99%
“…Thus, we analyzed potential correlations between the genes encoding lysosomal enzymes and their activities. Recently we described the natural variation of hepatic acid β-glucocerebrosidase levels across many different mouse strains and included them in this analysis 26 . We did not identify significant correlations between enzyme activity and its transcript levels (Fig.…”
Section: Lack Of Correlation Between the Enzyme Activity And Its Mrna...mentioning
confidence: 99%
“…Genome-wide association studies (GWAS) in humans and systems genetics strategies, which include gene mapping in model organisms, have identified genetic regulators of physiological and pathophysiological processes [26][27][28] . The Hybrid Mouse Diversity Panel (HMDP) has been a useful tool because genomes and tissue transcriptomes are freely available, allowing the combination of modifier gene mapping by GWAS and pathway analysis 29 .…”
Section: Introductionmentioning
confidence: 99%